Impact of Quality Service Delivery Challenges on Customer Satisfaction in the Banking Industry: A Case of Stanbic Bank, Zambia - Mukelabai , Namakau; Mulungu, Choongo (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
Since Zambia's 1991 economic liberalization, there has been notable growth in the retail banking sector. Quality search is perhaps the most critical consumer trend in recent years because consumers are now more demanding than ever. Customers have diverse options in an era of rapid global change, often relying on brand names for complex financial services. Hence, it becomes imperative to delve into the challenges surrounding quality service delivery and customer satisfaction. A mixed methods approach was adopted, and involved 340 bank customers who attended a questionnaire and 20 customers and bank staff who participated in in-depth interviews. . The study found that the majority (43.8%) of customers were generally satisfied with the services at the bank. The study also found that tangibility and assurance were the service quality dimensions that highly influenced customer satisfaction perception at Stanbic Bank. Tangibility had a positive influence on customer satisfaction (β=0.153), and a p-value (0.028) less than the selected level of significance (0.05), an indication of the influence of tangibility on customer satisfaction. The study concluded that customer satisfaction and loyalty depended on the quality of services the bank provided. At the same time, the study's practical implications suggest that the bank should focus on improving reliability, responsiveness, and empathy to enhance customer satisfaction.